1983: Annual National Conference on Learning Skills and Communication: Communication, Learning and Literacy at Tertiary Level - Chan (Convenor), Gloria (Journal of Academic Language and Learning, 2026)
Notes: 1. The page numbers below refer to the file page number, not the number on the page. 2. In the pdf, an article can be accessed directly by clicking on its title in the table of contents or via the Bookmarks pane. Learning Skills and Performance: Glen Evans … 3 Improving the Performance of Students: A Job for the Faculty … 19 Science Faculty Orientation Programme Questionnaire … 35 Mature Age Students: How Different? Brigid Ballard … 39 Opening the Doors to Higher Education: V. J. Beasley … 43 A Rightful Place for Order: R. S. Meyo … 48 Learning to Study Despite Being a Student: You've Got to have a System: Paul Hetherington … 61 Giving Credit Where Credit's Needed: A Proposed Course in Tertiary Learning Skills: Len Unsworth … 70 Teaching Information Skills: Whose Responsibility? - a discussion paper: Lee W. Andresen … 80 Learning Skills in a Disciplinary Context: Some Working Models: Leith Hancock and John A. Bowden … 98